Reflections about School Finance Education activities for Youth and Adult Education - Silva, Arlam Dielcio Pontes da; Carvalho , Liliane Maria Teixeira Lima de; Pessoa , Cristiane Azevedo dos Santos (Educação Matemática Debate, 2024)
Our aim is to identify, in the light of Critical Mathematics Education, elements in the work O Auto da Compadecida that promote an invitation to reflect on School Financial Education with students from the first modules of Educação de Jovens e Adultos (Youth and Adult Education — EJA). We used the ideas of backgrounds, foregrounds and scenarios for investigating Critical Mathematics Education to create four activities based on the episodes of the miniseries O Auto da Compadecida, with questions that allow the researcher to invite students to explore their experiences, perspectives and social problems. We believe that it is important for EJA students to be prepared to not only receive information or concepts about finance, but above all to develop the skills to interpret, analyze, reflect, have an opinion, discuss ideas and make decisions.